Penggunaan Media Promosi Online Dalam Meningkatkan Kualitas Penjualan Produk Frozen Food Pada UKM Dapoer Mama Ana - Fadillah Rezky, Syarifah; Hamdani, Rita; Suherdi , Devri; Sari, Kartika; Syahputri, Astri (Jurnal Masyarakat Indonesia (Jumas), 2023)
Dapoer Mama Ana is one of the home industries carried out by Mrs. Mariana Harahap in the city of Medan, Kelurahan Gedung Johor, Medan Johor District, North Sumatra Province, the Dapoer Mama Ana home industry produces a variety of frozen food, namely variants of dim sum skin, kebab skin, risol , dimsum, batagor, meatballs and nuggets. Dapoer Mama Ana has several problems, namely in the marketing management section, product packaging and business management. Based on the problems faced by the owner of Dapoer Mama Ana, we as a team limit the problems that exist with Dapoer Mama Ana, namely problems in marketing management. An example of a part of marketing is promotion, which is an activity that focuses on the efforts of entrepreneurs as a whole in increasing sales of products or services as well as in introducing their innovations. When the promotion is carried out, determining the promotional media is a very important aspect. All forms of promotional media must be able to accommodate the objectives of the promotion, both as an effort to increase sales results and as an effort to develop a business brand image. Therefore, this Community Service will focus on the use of online promotional media in the form of branding on Dapoer Mama Ana.